Dietary Patterns and Fractures Risk in the Elderly - Colica, Carmela; Mazza, Elisa; Ferro, Yvelise; Fava, Antonietta; De Bonis, Daniele; Greco, Marta; Foti, Daniela Patrizia; Gulletta, Elio; Romeo, Stefano; Pujia, Arturo; Montalcini, Tiziana (Frontiers in Endocrinology, 2017)
Purpose: Although the role of dietary factors in the prevention of bone loss and fractures has been investigated in many studies, few studies have examined the association between dietary patterns and total body bone density. Our aim was to determine the relations between dietary patterns and whole-body bone mineral density and the association between dietary patterns, fractures and multiple fractures in the elderly. Methods: This cross-sectional study included 177 individuals aged ≥ 65 years. A DXA scan was performed to measure bone mineral density. Dietary patterns were ascertained by a combination of dietary intake assessment and Principal Components Analysis. Results: Only 3 dietary patterns correlated with whole-body bone density. The multivariate-adjusted mean bone density across tertiles of these dietary patterns showed that the highest tertile of both the patterns 1 and 2 had a significantly higher bone density than the lowest tertile (pattern 1: 1.021±0.01 and 1.070±0.01g/cm2 for T1 and T3 respectively; p=0.043; pattern 2: 1.023±0.01, and 1.081±0.01g/cm2 for T1 and T3 respectively; p= 0.003). We also find significant gender difference in these results. The highest adherence to the dietary pattern 5 was associated with decreased odds of having fractures (OR=0.20, p=0.009) and adherence to the pattern 1 was negatively associated with multiple fractures. Conclusion: A high adherence to the dietary pattern 1 (high intake of grains, fish and olive oil) was associated with a high bone mineral density and a low number of fractures. The highest adherence to the dietary pattern 5 (legumes and wine) was associated with decreased odds of having fractures. Our finding would suggest a potential bone-preserving properties of specific dietary patterns in the elderly.